Biochemical oxidative stress-related markers in patients with obstructive sleep apnea - Volná, Jana; Kemlink, David; Kalousová, Marta; Vávrová, Jana; Majerová, Veronika; Mestek, Otto; Svarcová, Jana; Sonka, Karel; Zima, Tomás (Medical Science Monitor, 2011)
BACKGROUND: Obstructive sleep apnea (OSA) is a condition contributing to oxidative stress. The aim of this study was to ascertain if there is any connection between OSA and novel oxidative stress-related markers. Matrix metalloproteinases 2 and 9 (MMP-2, MMP-9), high sensitive C-reactive protein (hsCRP), pregnancy-associated plasma protein-A (PAPP-A), soluble receptors for advanced glycation end-products (sRAGE), zinc (Zn) and copper (Cu) were measured. Further biochemical markers were evaluated. MATERIAL/METHODS: Fifty-one men suspected for OSA indicated for night polygraphy were included. Apnea/hypopnea index (AHI), oxygen desaturation index (ODI), mean blood hemoglobin oxygen saturation (SpO2) and time of blood hemoglobin oxygen saturation below 90% (SpO2 <90%) were measured. Morning venous blood samples were taken. RESULTS: For body mass index (BMI) we found strong positive correlation with levels of Cu, MMP-9, hsCRP and fibrinogen, and negative correlation with sRAGE. Concerning ventilation parameters, we found positive correlation of ODI and SpO2 <90% with markers MMP-9 and hsCRP. sRAGE level correlated with AHI and ODI negatively. SpO2 correlated negatively with Cu, MMP-9, hsCRP and fibrinogen. There was no correlation between ventilation parameters and markers MMP-2, PAPP-A and Zn. Compared to severity of OSA, there was significant difference in levels of hsCRP and Cu between patients with AHI ≤5 and AHI ≥30 independent of BMI. CONCLUSIONS: MMP-9, hsCRP, sRAGE and Cu seem to be strong predictors of oxidative stress in OSA patients. The strong correlation between oxidative stress-related markers and OSA is elucidated by connection of these to BMI, which is probably a primary condition of oxidative stress, but OSA is an additive condition.
Keywords: biologické markery; lidé; Middle Aged; Adult; Oxidative Stress; C-reaktivní protein; Humans; lidé středního věku; Biomarkers; mužské pohlaví; Sleep Apnea, Obstructive; obstrukční spánková apnoe; měď; oxidační stres; Matrix Metalloproteinase 9; Oxygen; Male; kyslík; C-Reactive Protein; dospělí; matrixová metaloproteinasa 9; Copper